2008
DOI: 10.1186/1757-1626-1-144
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline-induced ulceration mimicking esophageal cancer

Abstract: Introduction: Doxycycline-induced esophageal ulcer patients are mostly young persons with no history of esophageal dysfunction. Heartburn, midsternal pain and dysphagia are the most common symptoms. It has generally a benign course. The present case is the first report of doxycyclineinduced extensive ulcerations, mimicking esophageal cancer in two esophageal segments alongside, in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 5 publications
2
15
0
Order By: Relevance
“…In the upper endoscopy, we found that most of the ulcers were located in the middle third of the esophagus, which is compatible with the literature (2,13). Although the histopathological examination of PE is rarely pathognomonic, it is generally nonspecific and includes mostly benign ulcer and acute inflammatory changes (12,16,(22)(23)(24). However, histological evaluation should be performed for differential diagnosis, especially in cases where malignancy and infectious pathologies are suspected.…”
supporting
confidence: 88%
“…In the upper endoscopy, we found that most of the ulcers were located in the middle third of the esophagus, which is compatible with the literature (2,13). Although the histopathological examination of PE is rarely pathognomonic, it is generally nonspecific and includes mostly benign ulcer and acute inflammatory changes (12,16,(22)(23)(24). However, histological evaluation should be performed for differential diagnosis, especially in cases where malignancy and infectious pathologies are suspected.…”
supporting
confidence: 88%
“…Crohn's disease) or esophageal cancer as in some patients esophageal lesions may appear endoscopicaly as malignant lesions. [16] In most cases treatment of pill-induced esophagitis implies discontinuing the causative agent. In order to prevent such injuries or for patients who wish/have to continue these treatments the risk of esophageal lesions can be reduced by taking medications with 200-250 ml of water, taking medications if possible in the morning and remaining in upright position for at least 30 min after swallowing the tablet or until food is ingested.…”
Section: Medication Inducing Esophageal Injurymentioning
confidence: 99%
“…Iron tablets [2], doxycycline [3], cyproterone acetate and ethinylestradiol [4] are all described to have led to painful esophagitis. Even a presentation of esophageal cancer-like symptoms after doxycycline intake is described by Tahan et al [5]. There is little information regarding discoloration of the gastric antrum and duodenal bulb, despite their known propensity to be a hot spot for bleedings, ulcerations, and tumors.…”
Section: Discussionmentioning
confidence: 99%